The Assessment of Financial Literacy: The Case of Europe - Nicolini, Gianni (International Review of Financial Consumers, 2019)
The study starts from the definition of financial literacy and its components, to identify the criteria that an assessment methodology should have to properly measure it. In the second part, an empirical analysis of the degree of financial literacy of adult population in several European countries (France, Germany, Italy, Sweden, UK) is used to highlight similarities and to stress differences between countries. Results show how the availability of 50 items allows to differentiate the levels of financial literacy in various areas of knowledge (e.g. loans, investments, money management). The use of money (e.g. credit cards, debit cards, cash) is the area of knowledge where individuals seem to be more well-informed and confident. Conversely, investment and investment products (e.g. stock, bonds) represent a weak point, with average scores being dramatically low.